Late Pleistocene/Early Holocene Migratory Behavior of Ungulates Using Isotopic Analysis of Tooth Enamel and Its Effects on Forager Mobility. - Suzanne E Pilaar Birch; Preston T Miracle; Rhiannon E Stevens; Tamsin C O'Connell (PLoS ONE, 2016)
Zooarchaeological and paleoecological investigations have traditionally been unable to reconstruct the ethology of herd animals, which likely had a significant influence on the mobility and subsistence strategies of prehistoric humans. In this paper, we reconstruct the migratory behavior of red deer (Cervus elaphus) and caprids at the Pleistocene-Holocene transition in the northeastern Adriatic region using stable oxygen isotope analysis of tooth enamel. The data show a significant change in δ18O values from the Pleistocene into the Holocene, as well as isotopic variation between taxa, the case study sites, and through time. We then discuss the implications of seasonal faunal availability as determining factors in human mobility patterns.